Hierarchical MAS Based Control Strategy for Microgrid - Xiao, Zhe; Li, Tinghua; Huang, Ming; Shi, Jihong; Yang, Jingjing; Yu, Jiang; Wu, Wei (Energies (Basel), 2010)
Microgrids have become a hot topic driven by the dual pressures of environmental protection concerns and the energy crisis. In this paper, a challenge for the distributed control of a modern electric grid incorporating clusters of residential microgrids is elaborated and a hierarchical multi-agent system (MAS) is proposed as a solution. The issues of how to realize the hierarchical MAS and how to improve coordination and control strategies are discussed. Based on MATLAB and ZEUS platforms, bilateral switching between grid-connected mode and island mode is performed under control of the proposed MAS to enhance and support its effectiveness.